2022
DOI: 10.1155/2022/4541533
|View full text |Cite|
|
Sign up to set email alerts
|

The Construction of Folk Sports Featured Towns Based on Intelligent Building Technology Based on the Internet of Things

Abstract: With the emergence of the Internet of Things, technology and Internet thinking have entered traditional communities, and combined with traditional technologies, many new and better management methods and solutions have been born. Among them, the concept of intelligent buildings is also known to people. Based on big data technology, cloud computing technology, and Internet of Things technology, smart buildings provide smart and convenient devices and services for smart device users. The Internet of Things techn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…(4) The theory of "strategy" holds that the size of the core competitiveness of an enterprise depends on whether the strategic layout of the company is appropriate, and whether the strategic layout is successful or not is the embodiment of the core competitiveness of the enterprise. (5) The theory of "capability" evaluates whether an enterprise can have unique capabilities in a certain field, such as resource development, product innovation, and market share, from the perspective of the enterprise as a whole [7][8][9]. Whether it has long-term and effective competitiveness, the author believes that core competence is a complex concept, which is not determined by a single factor, but the embodiment of the comprehensive ability of an enterprise or individual.…”
Section: Research Methods and Concepts Ofmentioning
confidence: 99%
“…(4) The theory of "strategy" holds that the size of the core competitiveness of an enterprise depends on whether the strategic layout of the company is appropriate, and whether the strategic layout is successful or not is the embodiment of the core competitiveness of the enterprise. (5) The theory of "capability" evaluates whether an enterprise can have unique capabilities in a certain field, such as resource development, product innovation, and market share, from the perspective of the enterprise as a whole [7][8][9]. Whether it has long-term and effective competitiveness, the author believes that core competence is a complex concept, which is not determined by a single factor, but the embodiment of the comprehensive ability of an enterprise or individual.…”
Section: Research Methods and Concepts Ofmentioning
confidence: 99%
“…The majority of platforms relevant to cloud computing are suppliers of shared resources. Application administration, measurement content delivery, and preservation costs have been dramatically lowered because servers no longer need to sit idle for extended periods [31,32]. Although past studies have explored cloud computing advantages, more effort has yet to be performed to evaluate the usage of cloud computing in the emerging world's building industry nations.…”
Section: Introductionmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%